2016
DOI: 10.2217/pgs.15.166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-509–3p Increases the Sensitivity of Epithelial Ovarian Cancer Cells to Cisplatin-Induced Apoptosis

Abstract: Our data suggest that restoring certain dysregulated miRNAs to their normal levels could increase the therapeutic effects of anticancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…MiR-509-3p has been reported to act as a tumour suppressor by inhibiting gastric cancer cell proliferation and migration, and its overexpression was shown to induce apoptosis and inhibit breast and lung cancer cell invasion 33 , 34 . MiR-509-3p was found to suppress metastasis in breast cancer cells and increase the sensitivity of epithelial ovarian cancer cells to cisplatin-induced apoptosis 35 . It was also recently reported that miR-509-3p directly targets YAP and miR-509-3p mimic decreased YAP expression, thereby suppressing migration of ovarian cancer cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-509-3p has been reported to act as a tumour suppressor by inhibiting gastric cancer cell proliferation and migration, and its overexpression was shown to induce apoptosis and inhibit breast and lung cancer cell invasion 33 , 34 . MiR-509-3p was found to suppress metastasis in breast cancer cells and increase the sensitivity of epithelial ovarian cancer cells to cisplatin-induced apoptosis 35 . It was also recently reported that miR-509-3p directly targets YAP and miR-509-3p mimic decreased YAP expression, thereby suppressing migration of ovarian cancer cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-509-3p has been reported to sensitize ovarian cancer cells to cisplatin treatment by targeting multiple anti-apoptosis genes including BCL2 [129,130] . Niu et al [131] compared the expression profiles of miRNAs between three pairs of platinum-resistant and platinum-sensitive ovarian tissues and found that miR-509-3p was significantly down-regulated in cisplatin-resistant ovarian cancer tissues.…”
mentioning
confidence: 99%
“…After seeding onto a 48-well plate, OVCAR3 cells were transfected with miR-146a-5p mimic, mimic control, miR-146a-5p inhibitor or inhibitor control. Cisplatin treatment and DAPI staining were performed as previously described (43). Our results show that more apoptotic nuclei were observed in OVCAR3 cells transfected with miR-146a-5p mimic compared to mimic control ( Fig.…”
Section: Transfection Of Rna Oligonucleotidesmentioning
confidence: 54%